Preference for Lighting Chromaticity in Migraine With Aura. Issue 6 (13th April 2020) - Vieira, Alexandra; van der Linde, Ian; Bright, Peter; Wilkins, Arnold
Abstract : Objective: We studied the color of lighting chosen as comfortable for reading by individuals with migraine and controls. We explored the effects of the chosen color on visual performance. Background: It has been reported that individuals who experience migraine with aura (MWA) choose, as comfortable for reading, light that is more strongly saturated in color than that chosen by individuals without migraine. Methods: A convenience sample of 18 individuals who experienced MWA, 18 without aura, and 18 controls without migraine participated in a cross‐sectional laboratory study at Anglia Ruskin University. We used an Intuitive Colorimeter that illuminated text with colored light and permitted the separate control of hue (color) and saturation (strength of color) without a change in luminance. We selected individuals with migraine and healthy controls from the general population. They were headache‐free in the 48 hours prior to testing. We used a routine that permitted the selection of the most comfortable hue from 12 alternatives and then alternately optimized the saturation and hue using small changes, thereby allowing for color adaptation. Visual performance at a word search task was measured under white light and under light of a color chosen as comfortable, using colored lenses. Results: Healthy individuals chose light with chromaticity close to the Planckian locus, which approximates the chromaticities of daylight and most electric lighting. The distance from the locus averaged 0.029 (SD 0.021). Individuals who experienced MWA chose strongly saturated colors well away from the Planckian locus (average distance 0.056, SD 0.022). Individuals who experienced migraine without aura chose intermediate chromaticities (average distance 0.034, SD 0.022). Overall there was a large statistically significant difference between participant groups that explained 24% variance. Visual search time of individuals with migraine aura decreased from 22.5 to 16.8 s when light of the chosen color was provided using tinted lenses (the average increase in search speed was 45.7%). The lenses had no statistically significant effect on the performance of individuals without migraine aura. Conclusions: Individuals who experienced MWA selected as comfortable colors that deviated from the lighting typically experienced in everyday life. Possibly, individuals who experience MWA may be more susceptible to photophobia under typical lighting. Visual performance was improved using lenses that provided light of the chosen comfortable color. The spectral power of that choice showed no evident relationship to melanopic energy (energy captured by the intrinsically photosensitive retinal ganglion cells).